Rebellious mourning : the collective work of grief - Milstein, Cindy (AK Press, 2017)
"We can bear almost anything when it is worked through collectively. Grief is generally thought of as something personal and insular, but when we publicly share loss and pain, we lessen the power of the forces that debilitate us, while at the same time building the humane social practices that alleviate suffering and improve quality of life for everyone. Addressing tragedies from Fukushima to Palestine, incarceration to eviction, AIDS crises to border crossings, and racism to rape, the intimate yet tenacious writing in this volume shows that mourning can pry open spaces of contestation and reconstruction, empathy and solidarity. With contributions from Claudia Rankine, Sarah Schulman, David Wojnarowicz, Leanne Betasamosake Simpson, David Gilbert, and thirty-two others. Also includes a 32-page color insert featuring artists like Jet Chalk, Oree Originol, Melanie Cervantes and Jesus Barraza, and more."--Publisher website